Impact of Anxiety on Performance in Exam - YACHNA SURYAVANSHI, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Anxiety is a significant indicator of academic achievement. Test anxiety has a direct impact on a student's academic progress. Whenever a student questions himself and his capacity to perform well on tests, his primary concentration becomes worrying about poor grades and he is unable to focus on academics. People who have anxiety illnesses have a cautious approach towards their studies, like taking less interest while studying and worst results in tests and projects. This study investigates the association between students' educational achievement and their level of academic stress. Particularly, whether test anxiety prior to an exam influences students’ academic performance. This survey included 100 male and female students. The findings revealed a substantial link between test anxiety and exam grades. Furthermore, linear regression studies revealed that test anxiety could predict exam grades